Innovative cryptography - Moldovyan, Nick (Charles River Media, 2007)
Innovative Cryptography, Second Edition provides a cutting-edge evaluation and review of current findings in the area of cryptography and explores how to implement these new techniques efficiently. It covers current cryptographic problems and suggests practical solutions. The book also discusses the role of symmetric ciphers and symmetric block ciphers, and details the need for fast symmetric ciphers for hardware (DES), software (RC5, Blowfish), and universal (AES, RC6, Twofish, IDEA, GOST) implementations. In addition, the book covers the issues surrounding the development and design of software-oriented ciphers, including ciphers based on the algorithm formed depending on the secret key. Some specific issues related to the cryptographic strength of ciphers with the flexible algorithm of data transformation are considered, and a combinational probabilistic model is suggested for obtaining minimal evaluations of the software ciphers being considered.